EGALITE Newsletter : equality for gays and lesbians in the European institutions. - EGALITE (Brussels : EGALITE, 1994)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks ; vanaf (1997) 21 : driemaandelijks
Redactie : Wetstraat 200, 1049 Brussel
Engels
Periodiek